Perbedaan Fungsi Penggunaan Modalitas Nakerebanaranai, Beki dan Hazu dalam Komik Chibi Maruko Chan dan Detektif Conan - Fennie, Fennie; Novianti, Nalti (Lingua Cultura, 2010)
There are many grammatical category in Japanese language, one of them is grammaticalÂ category in predicate. For examples is modality. Modality has divided into many kinds, for examplesÂ is toui modality and gaigen modality. Between toui modality and gaigen modality, writer want toÂ analyze about differences uses between nakereba naranai ã€Œãªã‘ã‚Œã°ãªã‚‰ãªã„ã€, bekiã€Œã¹ãã€danÂ hazuã€Œã¯ãšã€. Article analyzes this topic because the writer want to understand about the differencesÂ using toui modality and gaigen modality. For analyze, the writer use Chibi Maruko Chan 9 andÂ Detektif Conan jilid 7, 9, 37 and 38 that used Japanese language as an object. The used methods inÂ this article is descriptive analytic. As a conclusion, these modality can substitute each others. ThisÂ substitutin is based on the situations and context.